Loss of phosphatidylserine flippase β-subunit Tmem30a in podocytes leads to albuminuria and glomerulosclerosis - Wenjing Liu; Lei Peng; Wanli Tian; Yi Li; Ping Zhang; Kuanxiang Sun; Yeming Yang; Xiao Li; Guisen Li; Xianjun Zhu (The Company of Biologists, 2021)
The asymmetric distribution of phosphatidylserine (PS) in the cytoplasmic leaflet of eukaryotic cell plasma membranes is regulated by a group of P4-ATPases (named PS flippases) and the β-subunit TMEM30A. Podocytes in the glomerulus form a filtration barrier to prevent the traversing of large cellular elements and macromolecules from the blood into the urinary space. Damage to podocytes can disrupt the filtration barrier and lead to proteinuria and podocytopathy. We observed reduced TMEM30A expression in patients with minimal change disease and membranous nephropathy, indicating potential roles of TMEM30A in podocytopathy. To investigate the role of Tmem30a in the kidney, we generated a podocyte-specific Tmem30a knockout (KO) mouse model using the NPHS2-Cre line. Tmem30a KO mice displayed albuminuria, podocyte degeneration, mesangial cell proliferation with prominent extracellular matrix accumulation and eventual progression to focal segmental glomerulosclerosis. Our data demonstrate a critical role of Tmem30a in maintaining podocyte survival and glomerular filtration barrier integrity. Understanding the dynamic regulation of the PS distribution in the glomerulus provides a unique perspective to pinpointing the mechanism of podocyte damage and potential therapeutic targets.